Evidence of Coulomb correction and spin-orbit coupling in rare-earth dioxides CeO2, PrO2 and TbO2: An ab initio study - Mohammed Benali, Kanoun; Ali Hussain, Reshak, Prof. Dr.; Nawel, Kanoun-Bouayed; Souraya, Goumri-Said (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/